Cognitive decline among older adults: A hidden preexisting condition and its role in 'brain‐at‐risk' surgical patients. Issue 5 (4th March 2021) - Brenna, Connor T. A.; Orser, Beverley A.; Avramescu, Sinziana; Fleet, Andrew; Kaustov, Lilia; Choi, Stephen
Abstract : Preexisting cognitive impairment is an important, but underrecognized, predictor of postoperative neurocognitive dysfunction, a common and important sequela of surgery. We have applied computerized neuropsychological testing as an efficient and reliable means of detecting preexisting cognitive impairment in two studies of cardiac and noncardiac surgical populations and propose that this tool has great potential in routine clinical diagnosis.